Digital innovation and banking regulation - Chryssafoula Papathanassiou (European Central Bank (ECB), 2024)
The European Union is aiming to foster digital transformation in all sectors by 2030. It has pioneered cross-sectoral legislation on artificial intelligence, cloud computing services and crypto-assets for this purpose. Yet compared with the work done on ESG, the prospective banking regulation regime has still to articulate more purposefully how the industry should manage the risks from digital trends and how supervisors should assess them. This paper discusses digital innovation in the banking sector in the context of the academic literature on financial innovation and non-banks. It also considers how to foster a risk-based Pillar 2 prudential framework, as well as market discipline through harmonised Pillar 3 disclosures. The paper concludes that these latter two propositions can help reconcile the challenges stemming from the short-term horizon applied in prudential assessment and the longer-term horizon over which digital innovation will take place in the banking sector.
Keywords: K23; K24; 330; digitalisation; artificial intelligence; crypto-assets; cloud computing; supervision